Evaluasi Pelepasan Informasi Medis Berdasarkan Aspek Hukum Keamanan dan Kerahasiaan Rekam Medis di Rumah Sakit Umum Daerah Sleman - 'Athiyyah yumna; Feby Erawantini; Wiwin Ida Nurjayanti (Politeknik Negeri Jember, 2021)
The release of medical information is a notification/provision of information about the health condition/illnes suffered by the patient and the risks that occur to the patient. There are several problems that exist in the process of releasing medical information to Jasa Raharja insurance in Sleman District Hospital including the absence of a power of attorney written by the patient or the patientâ€™s guardian (if the patient is unable to make a power of attorney) and incomplete information contained in the Standard Operating Procedures (SOP). The purpose of this research is to evaluate the release of medical information for Jasa Raharja insurance based on legal aspects of the security and confidentiality of medical records in PERMENKES No. 269 of 2008. This research is descriptive qualitative, with data collection techniques carried out by observing the implementation of the release of medical information for jasa raharjaâ€™s insurance claims, interviews with officers responsible for releasing medical information in RSUD Sleman, and documentation of SOP information release. The result of this research are new Standard Operating Procedures (SOP) recommendations related to the process of releasing medical information for Jasa Raharja insurance and new Standard Operating Procedures (SOP) socialization related to releasing medical information for Jasa Raharja insurance. SOP update is very important because it can maintain the security and confidentialityÂ of medical record files so that it cannot be misused by irresponsible parties.